Rekonstruksi Keberagamaan Santri Jawa - Ahidul Asror (Islamica: Jurnal Studi Keislaman, 2012)
This paper distinguishes first of all between Islam as a system of value?transcendental Islam that is?and Islam as socio-cultural phenomenon?sociological Islam that is. The former is about religion as a given system of belief, while the latter is about religious way of life. While touching briefly on the former, the paper will focus a great deal on the latter. It will focus as such on the ?constructed Islam? by the Javanese Muslim santris. Employing the social constructive theory, the paper assumes that these santris are active agents in building their own religiosity through what may be called a dialectical moment. Hence, the paper refuses the commonly believed understanding that social facts are completely outside individual awareness in the process of religious construction. By this, the paper attempts to show that Javanese Islam?sociologically speaking?is none other than the product of santri?s cultural and social upbringing.